Mozart, the wonder child : a puppet play in three acts - Stanley, Diane (New York : Collins, 2009)
Presents an illustrated portrait of Wolfgang Amadeus Mozart done in egg tempera artwork that features Mozart and other characters as marionettes in a puppet show.
Includes bibliographical references.
Booklist
Kirkus Review
4.6
3-6
3-6
Keywords: Mozart, Wolfgang Amadeus, -- 1756-1791 -- Juvenile literature; Mozart, Wolfgang Amadeus, -- 1756-1791.; Mozart, Wolfgang Amadeus, -- 1756-1791.; Composers -- Austria -- Biography -- Juvenile literature; Puppet plays; Composers; Puppet plays; Composers -- Biography; Puppets and puppet plays